Study of the photopolymerization process of luminescent-labeled photocurable compositions in liquid and gas media - Noworyta, Małgorzata; Pilch, Maciej; Kiesiewicz, Dawid; Kłaput, Renata; Ortyl, Joanna (Chemical and Process Engineering: New Frontiers, 2026)
Although photocurable compositions are widely used in 3D printing, protective coatings and biomedical materials, their polymerization in oxygen-containing environments is strongly hindered by oxygen inhibition, which prolongs the reaction time and reduces the conversion rate of monomers. This study investigated the effect of the reaction environment (argon atmosphere and liquid media: distilled water and CuSO4 solutions) on the kinetics of free-radical photopolymerization of four acrylic compositions (Bis GMA with TMPTA or EBECRYL 45, 130, 3300 oligomers). The kinetics were monitored using Fluorescence Probe Technology (FPT) with a coumarin 102 fluorescence probe and photorheology under 365 nm UV-LED irradiation. The results showed that in an argon atmosphere, oxygen inhibition is eliminated, resulting in the shortest induction times. In liquid environments, induction times are longer, but initial polymerization rates are higher than in the gas phase due to multiple reflections of UV radiation and a higher effective dose. The addition of Cu2+ ions partially suppresses this effect by absorbing light. The work provides new data on the design of photopolymerizable systems with increased oxygen resistance, which is important for applications in VPP photopolymerization 3D printing.